"Records in becoming" - Popovici, Bogdan-Florin (Moderna arhivistika, 2018)
The paper examines a concept "records in becoming" and its possible implications for archival management.In 1994, Sue McKemmish uses the same term, record in becoming, in order to assert that the record is never finished. Within the framework of Australian records continuum, she supports the idea that at every step in a record existence, at any interaction with people, systems, business process, that record acquire new meanings, annotations, significances, therefore is never finished. Using the same terms in archival literature brings, first of all, confusions and an explanation of the mindset and implications of the two usage is intended. On the other hand, for each case, archival management needs an updated approach, in order to preserve and to deliver the proper representation of record to the users.
Keywords: database; lastnosti zapisa; podatkovna zbirka; record property; records; zapisi